Exothermic reaction kinetics in high energy density Al-Ni with nanoscale multilayers synthesized by cryomilling - Oh, Minseok; Oh, Min Chul; Han, Deokhyun; Jung, Sang Hyun; Ahn, Byungmin (Metals, 2018)
The Al-Ni system is known as a high energy density materials (HEDM) because of its highly exothermic nature during intermetallic compound (IMC) formation. In this study, elemental Al and Ni powder were milled to explore the effect of cryomilling atmosphere on the microstructure and exothermic behavior. Scanning electron microscope (SEM) observations show continuous structural refinement up to 8 h of cryomilling. No IMC phase was detected in the X-ray diffraction (XRD) spectrum. Differential thermal analyzer (DTA) results show two exothermic peaks for 8 h cryomilled powder as compared to that of powder milled for 1 h. The ignition temperature of prepared powder mixture also decreased due to gradual structural refinement. The activation energy was also calculated and correlated with the DTA and SEM results. The cryomilled Al-Ni powder is composed of fine Al-Ni metastable junctions which improve the reactivity at a lower exothermic reaction temperature.
Keywords: Activation energy; Al-Ni; Cryomilling; Exothermic reaction; High energy density materials